Answer:
(0,5)
Step-by-step explanation:
we have
----> inequality A
----> inequality B
we know that
If a ordered pair is a solution of the system of inequalities, then the ordered pair must satisfy both inequalities of the system (makes true both inequalities)
Verify each ordered pair
Substitute the value of x and the value of y of each ordered pair in the inequality A and in the inequality B and then compare the results
case 1) (0,5)
For x=0,y=5
<em>Inequality A</em>
![2(0)+3(5) > 12](https://tex.z-dn.net/?f=2%280%29%2B3%285%29%20%3E%2012)
----> is true
so
The ordered pair satisfy inequality A
<em>Inequality B</em>
![0-5\leq 1](https://tex.z-dn.net/?f=0-5%5Cleq%201)
---> is true
so
The ordered pair satisfy inequality B
therefore
The ordered pair would be a solution of the system
case 2) (5,2)
For x=5,y=2
<em>Inequality A</em>
![2(5)+3(2) > 12](https://tex.z-dn.net/?f=2%285%29%2B3%282%29%20%3E%2012)
----> is true
so
The ordered pair satisfy inequality A
<em>Inequality B</em>
![5-2\leq 1](https://tex.z-dn.net/?f=5-2%5Cleq%201)
---> is not true
so
The ordered pair not satisfy inequality B
therefore
The ordered pair is not a solution of the system
case 3) (0,4)
For x=0,y=4
<em>Inequality A</em>
![2(0)+3(4) > 12](https://tex.z-dn.net/?f=2%280%29%2B3%284%29%20%3E%2012)
----> is not true
so
The ordered pair not satisfy inequality A
therefore
The ordered pair is not a solution of the system
case 4) (6,0)
For x=6,y=0
<em>Inequality A</em>
![2(6)+3(0) > 12](https://tex.z-dn.net/?f=2%286%29%2B3%280%29%20%3E%2012)
----> is not true
so
The ordered pair not satisfy inequality A
therefore
The ordered pair is not a solution of the system